2021
DOI: 10.1186/s40337-021-00425-5
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating symptoms are associated with the severity of premenstrual symptoms among university students, cross sectional study from Palestine

Abstract: Background Premenstrual syndrome (PMS) is considered one of the most prevailing disorders among childbearing age women that could considerably interfere with daily living activities life. PMS is underrecognized in Palestine. It is reported that binge eating symptoms are significantly related to premenstrual syndrome. In this regard, the study aimed to determine factors linked with premenstrual symptoms and to explore whether binge eating symptoms are linked with premenstrual syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…The overall PMS prevalence was found to be (94%). The most frequently reported psychological and physical premenstrual symptoms were depressed mood (45.7%) and anger feelings (42.3%), muscle, joint, abdominal and back pain (43%), respectively, which is consistent with other studies, that observed how anger/irritability is the most frequently reported psychological symptom while abdominal pain was the most commonly observed physical symptom [ 19 ]. Moreover, in a Jordanian study, depression and mood swings were commonly reported PMS symptoms before menstruation [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…The overall PMS prevalence was found to be (94%). The most frequently reported psychological and physical premenstrual symptoms were depressed mood (45.7%) and anger feelings (42.3%), muscle, joint, abdominal and back pain (43%), respectively, which is consistent with other studies, that observed how anger/irritability is the most frequently reported psychological symptom while abdominal pain was the most commonly observed physical symptom [ 19 ]. Moreover, in a Jordanian study, depression and mood swings were commonly reported PMS symptoms before menstruation [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…are associated with a higher risk of developing eating disorder symptoms [98,99]. In addition, among women with binge eating symptoms, the occurrence of moderate and severe physical and psychological PMS symptoms was significantly more common, while no association between binge eating disorders and either PMS or PMDD was found.…”
Section: Managing Pmsmentioning
confidence: 90%
“…Another study showed a significantly higher EAT-26 score and overall prevalence of eating disorders in the group with PMDD than in the group with moderate-to-severe, mild, or no PMS symptoms [ 97 ]. It has also been suggested that physical and psychological PMS symptoms are associated with a higher risk of developing eating disorder symptoms [ 98 , 99 ]. In addition, among women with binge eating symptoms, the occurrence of moderate and severe physical and psychological PMS symptoms was significantly more common, while no association between binge eating disorders and either PMS or PMDD was found.…”
Section: Pms and Eating Behaviorsmentioning
confidence: 99%
“…O estrógeno, entre outras funções, atua como um protetor da saúde mental, contribuindo para que as mulheres fiquem mais ativas e com maior estabilidade de humor. Quando a produção deste hormônio cai, tem-se maior probabilidade de alterações do humor, aumento da tristeza, angústia e agressividade, predispondo-as a depressão e outros transtornos como as distimias (MACHADO, 2022;KANDEL, 2014;BEAR et al, 2008) Para Badrasawi et al (2021) Com isso, a revisão da literatura demonstra que o assunto está longe de um consenso, com controvérsias sobre os fatores de risco e de proteção envolvidos, bem como sobre o nível de limitação que a SPM traz para a vida das mulheres (AMB, 2011). Porém, é um tema de elevada relevância para a pesquisa médica e para a sociedade como um todo, necessitando mais estudos na área a fim de alcançar resultados e informações mais concretas e menos ruidosas.…”
Section: Discussionunclassified